The loss of glycocalyx integrity impairs complement factor H binding and contributes to cyclosporine-induced endothelial cell injury - Teoh, Chia Wei; Riedl Khursigara, Magdalena; Ortiz-Sandoval, Carolina G.; Park, Jee Woo; Li, Jun; Bohorquez-Hernandez, Arlette; Bruno, Valentina; Bowen, Emily E.; Freeman, Spencer A.; Robinson, Lisa A.; Licht, Christoph (Frontiers in Medicine, 2023)
Background: Calcineurin inhibitors (CNI) are associated with nephrotoxicity, endothelial cell dysfunction and thrombotic microangiopathy (TMA). Evolving evidence suggests an important role for complement dysregulation in the pathogenesis of CNI-induced TMA. However, the exact mechanism(s) of CNI-induced TMA remain unknown. Methods: Using blood outgrowth endothelial cells (BOECs) from healthy donors, we evaluated the effects of cyclosporine on endothelial cell integrity. Specifically, we determined complement activation (C3c, C9) and regulation (CD46, CD55, CD59 and complement factor H [CFH] deposition) as it occurred on the endothelial cell surface membrane and glycocalyx. Results: We found that exposing the endothelium to cyclosporine resulted in a dose and time dependent enhancement of complement deposition and cytotoxicity. We therefore employed flow cytometry, Western blotting/CFH cofactor assays, and immunofluorescence imaging to determine the expression of complement regulators and the functional activity and localization of CFH. Notably, while cyclosporine led to the upregulation of complement regulators CD46, CD55, and CD59 on the endothelial cell surface, it also diminished the endothelial cell glycocalyx through shedding of heparan sulfate side chains. The weakened endothelial cell glycocalyx resulted in decreased CFH surface binding and surface cofactor activity. Conclusion: Our findings confirm a role for complement in cyclosporine-induced endothelial injury and suggest that decreased glycocalyx density, induced by cyclosporine, is a mechanism leading to complement alternative pathway dysregulation via decreased CFH surface binding and cofactor activity. This mechanism may apply to other secondary TMAs – in which a role for complement has so far not been recognized – and provide a potential therapeutic target and an important marker for patients on calcineurin inhibitors.